Perceptions of Home Insurance and Policy Directions: Comparing Mexican Americans and Non‐Hispanic White Americans. Issue 2 (10th October 2019) - Zolfagharian, Mohammadali; Hasan, Fuad; Motie, Golnaz B.; Squires, Gregory D.
Abstract : With prior research on home insurance largely focused on supply side practices, we know little about demand side attributes of this market, especially about consumer perceptions of insurance. This article demonstrates that, despite seemingly more equitable industry practices, ethnic homeowners (Mexican Americans in this study), relative to the majority White population, have a greater tendency to view home insurance as a cost burden (as opposed to coverage against potential damages and injuries) and, hence, are more vulnerable to living with minimal or no home insurance coverage. The findings suggest that this disparity is attributable to cultural differences rooted in diverse structural and institutional circumstances in which ethnic homeowners often find themselves situated. The role of ethnic identity is salient even after accounting for personal, household, property, mortgage, and natural calamity factors. New directions for policy are proposed to address the situation by informing and empowering vulnerable consumers.